2021
DOI: 10.3389/fimmu.2021.699336
|View full text |Cite
|
Sign up to set email alerts
|

A Straightforward Method for 3D Visualization of B Cell Clusters and High Endothelial Venules in Lymph Nodes Highlights Differential Roles of TNFRI and -II

Abstract: Whole mount tissue immunolabeling and imaging of complete organs has tremendous benefits in characterizing organ morphology. Here, we present a straightforward method for immunostaining, clearing and imaging of whole murine peripheral lymph nodes (PLNs) for detailed analysis of their architecture and discuss all procedures in detail in a step-by-step approach. Given the importance of tumor necrosis factor receptor (TNFR) signaling in development of PLNs we used TNFRI-/- and TNFRII-/- mice models as proof-of-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The nucleolar signals were captured using the Z-stack function (5 × 1 µm Z-slices). The 3D rendering and volume measurements were performed using the SURFACE function in Imaris software [34,35].…”
Section: Confocal Microscopymentioning
confidence: 99%
“…The nucleolar signals were captured using the Z-stack function (5 × 1 µm Z-slices). The 3D rendering and volume measurements were performed using the SURFACE function in Imaris software [34,35].…”
Section: Confocal Microscopymentioning
confidence: 99%
“…Scientific literature survey shows that the majority of the articles on 3D analysis of vascular networks in optically cleared organs use commercial software, allowing the automatic segmentation of the vascular network, regardless of the thresholding technique associated. 4 , 5 , 13 , 14 In addition with commercial software, some laboratories have developed their own segmentation algorithms or computational tools to extract and quantify vasculatures. 6 , 15 , 16 , 17 Finally, around fifteen thresholding techniques are available with the open-source freeware ImageJ, belonging to 3 categories of the Sezgin and Sankur’s classification, based on 1 the shape of the pixel gray-level histogram (the properties of the gray-level histogram such as its peaks and valleys), (2) the clustering analysis of the pixel gray-level histogram (the gray-level histogram is considered as corresponding to two clusters of pixels representing the object and the background), and (3) the entropy of the pixel gray-levels of the image (the image is considered as composed of “information” associated to the signal but mainly of noise, with a certain degree of uncertainty on which gray-level correspond to what).…”
Section: Image Processingmentioning
confidence: 99%
“…A survey of the literature on optical clearing and 3D imaging of vascular networks indicates that the most of the articles use, for the segmentation step, Imaris software (Bitplane, Switzerland) FilamentTracer function. It has have been used to isolate the vascular network in several organs such as the heart, 4 the liver and the lung, 5 the pancreas, 13 the brachial and inguinal skeletal muscles, 14 and the kidney. 9 Imaris is a commercial software allowing 3D and 4D image analysis, and FilamentTracer is an extension initially allowing the automatic tracing of neurons and the detection of their spines, but extended for the tracing of any filamentous structures as blood vessels.…”
Section: Image Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed defects seem mainly dependent on TNFRI signaling, as mice lacking TNFRI have an abnormal SLO morphology, which is comparable to TNF −/− mice. This morphology includes aberrant architecture of lymphoid follicles, as mice lacking TNFRI have a peripheral B cell sheet rather than individual lymphoid follicles [7,8]. We recently demonstrated that PLNs (brachial and inguinal) of TNFRII −/− mice have a morphology reminiscent of TNFRI −/− mice, since PLNs of these mice have decreased individual lymphoid follicles, suggesting a previously unknown role for TNFRII signaling in SLO architecture [8].…”
Section: Introductionmentioning
confidence: 99%